Supply chain innovation and financial performance in ASEAN manufacturing firms: The moderating role of organisational innovation - Minh Hue Nguyen; Hang Thu Hoang; Dung Van Nguyen; Canh Huynh Quang Trinh (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This study investigates the relationship between supply chain innovation and financial performance in ASEAN manufacturing firms. Also, the study examines the moderating effect of organisational innovation in facilitating the impact of supply chain innovation on financial performance. The study utilises data regarding supply chain innovation, firm financial performance, and organisational innovation collected from the WorldBank Enterprise Survey. We employ the multilevel mixed-effects linear model to analyse the hierarchical data structure. The results confirm the important role of supply chain innovation in improving firms’ financial performance in ASEAN countries. Moreover, organisational innovation significantly moderates the relationship between supply chain innovation and firms’ financial performance.